Answer:
[tex]\displaystyle f(x) = \sum^{\infty}_{n = 0} \frac{x^{24n}}{[(2n)!]^2}[/tex]
General Formulas and Concepts:
Calculus
Sequences
Series
Power Series
Step-by-step explanation:
We are given the function:
[tex]\displaystyle f(x) = [cos(x^6)]^2[/tex]
Recall that the power series for cos(x) is:
[tex]\displaystyle cos(x) = \sum^{\infty}_{n = 0} \frac{(-1)^n x^{2n}}{(2n)!}[/tex]
To find the power series for cos(x⁶), substitute in x = x⁶:
[tex]\displaystyle cos(x^6) = \sum^{\infty}_{n = 0} \frac{(-1)^n (x^6)^{2n}}{(2n)!}[/tex]
Simplifying it, we have:
[tex]\displaystyle cos(x^6) = \sum^{\infty}_{n = 0} \frac{(-1)^n x^{12n}}{(2n)!}[/tex]
Rewrite the original function:
[tex]\displaystyle f(x) = \bigg[ \sum^{\infty}_{n = 0} \frac{(-1)^n x^{12n}}{(2n)!} \bigg]^2[/tex]
Simplify:
[tex]\displaystyle f(x) = \sum^{\infty}_{n = 0} \frac{(-1)^{2n} x^{24n}}{[(2n)!]^2}[/tex]
Simplify down further:
[tex]\displaystyle f(x) = \sum^{\infty}_{n = 0} \frac{x^{24n}}{[(2n)!]^2}[/tex]
And we have our final answer.
Topic: AP Calculus BC (Calculus I + II)
Unit: Power Series
Book: College Calculus 10e